Perancangan Pembuatan Maket Ruang Guru Pada Sekolah Budi Agung Medan - Rani Hermita; Juli Atika; Ajeng Resti Ajilah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
A mockup is a miniature or model of a building that will be made or has already been made, in order to facilitate visualization of the design results. Either in the form of a structural design, interior, exterior or site plan. The Budi Agung Medan School teacher's room is a teacher's room in a private school building. This site was chosen because the space in the design object requires spatial adaptation to accommodate new user activities. Apart from that, in terms of changes in working systems, uncomfortable circulation, insufficient storage requirements, and the image of the teacher's room is not yet prominent, these are the problems found. Apart from that, this is a limitation in designing the design. The Budi Agung Medan School teacher's room is a teacher's room in a private school building. This site was chosen because the space in the design object requires spatial adaptation to accommodate new user activities. Apart from that, in terms of changes in working systems, uncomfortable circulation, insufficient storage requirements, and the image of the teacher's room is not yet prominent, these are the problems found. Apart from that, this is a limitation in designing the design